Pengaruh Literasi Keuangan Dan Kemampuan Manajerial Terhadap Kinerja IMK Usaha Makanan Di Kabupaten Semarang - Bonifatius Junianto Wibowo; Ignatius Supriyanto; Widuri Kurniasari (JEMAP, 2023)
Financial Literacy and Managerial Competence are two things that can contribute to the performance of a business, including in the Micro Small Industry sector. This research was conducted to review the influence of financial literacy and managerial competence on the performance of food processing small and micro industry   in Semarang Regency. The data in this study are primary data regarding financial literacy, managerial competence, and business performance, which were obtained from 30 food processing small and micro industries in Semarang Regency as respondents. Respondents' answers are in the form of opinions obtained from various answers available on the questionnaire. The available answers are measured by a Likert scale. Before the respondent chooses the answer, first the answer is tested for validity and reliability. Collected data, then analysed using t test. Based on the results of the t test, it was found that financial literacy had no effect on business performance. On the other hand, managerial competence affects business performance. Based on this research, managerial competence can be said to be the key that can determine the level of business performance of food processing small and micro industries in Semarang Regency.